Uncovering the viral aetiology of undiagnosed acute febrile illness in Uganda using metagenomic sequencing - Ashraf, Shirin; Jerome, Hanna; Bugembe, Daniel Lule; Ssemwanga, Deogratius; Byaruhanga, Timothy; Kayiwa, John Timothy; Downing, Robert; Salazar-Gonzalez, Jesus F.; Salazar, Maria G.; Shepherd, James G.; Wilkie, Craig; Davis, Chris; et al. (Nature Publishing Group UK, 2025)
Abstract Viruses associated with acute febrile illness in Africa cause a spectrum of clinical disease from mild to life-threatening. Routine diagnostic methods are insufficient to identify all viral pathogens in this region. In this study, 1281 febrile Ugandan patients were prospectively recruited as part of the CDC-UVRI Acute Febrile Illness Study and pre-screened for common pathogens. 210/1281 undiagnosed samples, and 20 additional samples from viral outbreaks were subjected to metagenomic sequencing. Viral pathogens were identified in 44/230 (19%), including respiratory, hepatitis, blood-borne, gastrointestinal and vector-borne viruses. Importantly, one case of Crimean-Congo haemorrhagic fever and two cases each of Rift Valley fever, dengue and yellow fever were detected in 7/230 (3%) of cases. Le Dantec virus, last reported in 1969, was also identified in one patient. The presence of high-consequence and (re-)emerging viruses of public health concern highlights the need for enhanced population-based diagnostic surveillance in the African region.